Incidence of thrombosis in women caused by the use of oral hormonal contraceptives: a literature review (Research, Society and Development, 2022)
Thrombosis is considered a multifactorial disease, which happens when there is some imbalance in blood hemostasis. Hemostasis, which is nothing else, a normal physiological response of the body to prevent and stop bleeding and hemorrhages, maintains through regulatory mechanisms the blood in its fluid state inside the blood vessels, and ensure the blood supply in all parts of the body, to prevent the occurrence of bleeding and other complications, thus resulting in the blocking of any vascular injury. It is warned that the use of estrogens or contraceptive pills are risk factors to be considered regarding the inappropriate activation of normal hemostatic processes. It is evident that this relationship can be explained by the fact that estrogens and progestins decrease the blood clotting capacity and thus increase the pro-coagulant capacity of the coagulation cascade. Therefore, the present article seeks to correlate the incidence of thrombosis in the female population with the continuous use of hormonal contraceptives. Because, according to the research conducted by Silva; TOLEDO, a significant percentage of women who use oral contraceptives have acquired thrombosis over the years.